Reclaiming social work : challenging neo-liberalism and promoting social justice. - Ferguson, Iain, ....- (London : SAGE, 2008)
Reclaiming Social Work is a thought-provoking and innovative book which examines how social work's commitment to social justice has been deepened and enriched by its contact with wider social movements. It explores the tensions between social work values and a market-driven agenda, and locates new resources of hope for the social work profession in the developing resistance to managerialism. Key Features Discusses pertinent social work issues such as inequality and risk, the voluntary sector, and service-user involvement Examines values such as democracy, solidarity, accountability, participation, justice, equality, liberty and diversity Offers an accessible writing style, drawing on diverse examples to illustrate theoretical concepts. Reclaiming Social Work is an accessible yet challenging book and will be essential reading for all social work students and practitioners wanting to think outside the boundaries of their profession. The book will be particularly helpful to students taking courses in anti-oppressive practice, social work values, social work theories and concepts, and international social work.
Keywords: Neoliberalisme; Sociaal werk; Sociale rechtvaardigheid